1999
DOI: 10.1021/jp984570l
|View full text |Cite
|
Sign up to set email alerts
|

A Diode Laser and Modeling Study of Mixed (CH4−H2−O2) AC Plasmas

Abstract: Infrared diode laser spectroscopy has been used as a diagnostic probe to measure the concentrations of the methyl radical and stable products in an ac methane/hydrogen/oxygen (CH4−H2−O2) plasma. Among the products detected were all of the stable C-2 hydrocarbons and oxygen-containing species including methanol, formaldehyde, formic acid, carbon monoxide, and carbon dioxide. A simple one-dimensional chemical modeling program has been written to calculate and compare the model concentrations of all the detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 23 publications
0
57
0
Order By: Relevance
“…To add oxygen will yield OH radical and favor the CO ϩ OH 3 CO 2 ϩ H reaction, to lead to the reduction of S CO . 13 Figure 6 shows that the molar fraction of CO 2 apparently increased from 0.045 to 1.71% at 13.3 kPa, and increased only from 0.016 to 0.754% at 93.3 kPa, by increasing the O 2 /CH 4 ratio from 0.3 to 1.5 at 600 W.…”
Section: Byproduct Compositionsmentioning
confidence: 96%
See 3 more Smart Citations
“…To add oxygen will yield OH radical and favor the CO ϩ OH 3 CO 2 ϩ H reaction, to lead to the reduction of S CO . 13 Figure 6 shows that the molar fraction of CO 2 apparently increased from 0.045 to 1.71% at 13.3 kPa, and increased only from 0.016 to 0.754% at 93.3 kPa, by increasing the O 2 /CH 4 ratio from 0.3 to 1.5 at 600 W.…”
Section: Byproduct Compositionsmentioning
confidence: 96%
“…13,14 In addition, at a lower O 2 /CH 4 ratio, a much greater S H2 was found at 600 W than that at 160 W, whereas at a higher O 2 /CH 4 ratio, the S H2 was slight higher at 600 W than that at 160 W. By elevating the O 2 /CH 4 ratio from 0.5 to 1.5 at 600 W, experimental results showed that S H2 decreased significantly from 89.7 to 28.4% at 13.3 kPa, as well as decreasing from 97.6 to 29.4% at 93.3 kPa (Figure 2a). The large amounts of H 2 O, yielded at a higher O 2 /CH 4 ratio, led to a reduction of H 2 selectivity.…”
Section: Selectivities Of H 2 and Co At Different O 2 /Ch 4 Ratios Anmentioning
confidence: 99%
See 2 more Smart Citations
“…By applying the calculation process described in the previous section, we get the total dissociation rate constant. Then, the rate ratio of three following CH 4 dissociation reactions suggested by Fan et al (1999) …”
Section: Kinetic Parameters Of Electron-neutral Reactionsmentioning
confidence: 99%